Integrated metabolic strategy: A framework for predicting the evolution of carbon‐water tradeoffs within plant clades. (30th May 2019) - Goud, Ellie M.; Sparks, Jed P.; Fishbein, Mark; Agrawal, Anurag A.
Abstract: The fundamental tradeoff between carbon gain and water loss has long been predicted as an evolutionary driver of plant strategies across environments. Nonetheless, challenges in measuring carbon gain and water loss in ways that integrate over leaf lifetime have limited our understanding of the variation in and mechanistic bases of this tradeoff. Furthermore, the microevolution of plant traits within species versus the macroevolution of strategies among closely related species may not be the same, and accordingly, the latter must be addressed using comparative phylogenetic analyses. Here we introduce the concept of 'integrated metabolic strategy' (IMS) to describe the ratio between carbon isotope composition ( δ 13 C) and oxygen isotope composition above source water (Δ 18 O) of leaf cellulose. IMS is a measure of leaf‐level conditions that integrate several mechanisms contributing to carbon gain ( δ 13 C) and water loss (Δ 18 O) over leaf lifespan, with larger values reflecting higher metabolic efficiency and hence less of a tradeoff. We tested how IMS evolves among closely related yet ecologically diverse milkweed species, and subsequently addressed phenotypic plasticity in response to water availability in species with divergent IMS. Integrated metabolic strategy varied strongly among 20 Asclepias species when grown under controlled conditions, and phylogenetic analyses demonstrate species‐specific tradeoffs between carbon gain and water loss. Larger IMS values were associated with species from dry habitats, with larger carboxylation capacity, smaller stomatal conductance and smaller leaves; smaller IMS was associated with wet habitats, smaller carboxylation capacity, larger stomatal conductance and larger leaves. The evolution of IMS was dominated by changes in species' demand for carbon ( δ 13 C) more so than water conservation (Δ 18 O). Although some individual physiological traits showed phylogenetic signal, IMS did not. In response to experimental decreases in soil moisture, three species maintained similar IMS across levels of water availability because of proportional increases in δ 13 C and Δ 18 O (or little change in either), while one species increased IMS due to disproportional changes in δ 13 C relative to Δ 18 O. Synthesis. IMS is a broadly applicable mechanistic tool; IMS variation among and within species may shed light on unresolved questions relating to the evolution and ecology of plant ecophysiological strategies. Abstract : We introduce the concept of 'integrated metabolic strategy' to describe carbon‐water tradeoffs, as measured by the relationship between δ 13 C and Δ 18 O of leaf cellulose. We tested how integrated metabolic strategies evolve among closely related yet ecologically diverse milkweed species, and subsequently addressed phenotypic plasticity in response to water availability. Variation among and within species may shed light on previously unresolved questions relating to the evoluton and ecology of plant ecophysiological strategies.